PENERAPAN MODEL CIRCUIT LEARNING BERBANTUAN MEDIA GAMBAR TERHADAP HASIL BELAJAR IPS SISWA KELAS V SD NEGERI 50 LUBUKLINGGAU - Fajarsari. P, Diani Aulia; Frima, Aren; Yuneti, Armi (LP4MK STKIP PGRI Lubuklinggau, 2024)
This study aims to determine the completeness of social studies learning outcomes of grade V students of SD Negeri 50 Lubuklinggau after the application of the circuit learning model assisted by image media. The research method used is pre-experimental design. The population taken was all students of grade V of SD Negeri 50 Lubuklinggau and as a sample of class V which amounted to 28 students. The collection of dta is carried out by test technique. The collected data was analyzed using the z-test at a significant level of 0.05. So that zcalculate = 6,11and ztable = 1.64 (zcalculate≥ztable). Based on the analysis of the data of the last test, it can be concluded that the learning outcomes of students after participating in social studies learning with the circuit learning model assisted by image media have been significantly completed. Keywords: Learning Outcomes, Social Studies, Image Media, Circuit Learning Model